Inhibition of myeloid differentiation factor 2 by MAC28 suppresses reactive oxygen species, inflammation and improves mitochondrial function, leading to improved cardiac function in prediabetic rats. (14th October 2021) - Sumneang, N; Thun Oo, T; Singhanat, K; Maneechote, C; Arunsak, B; Nawara, W; Jaiwongkam, T; Pratchayasakul, W; Apaijai, N; Liang, G; Chattipakorn, S C; Chattipakorn, N
Abstract: Background: Chronic inflammation involves in the left ventricular (LV) dysfunction in high-fat diet (HFD)-induced prediabetes, along with cardiac mitochondrial dysfunction. This involved an activation of myeloid differentiation factor 2 (MD2)/toll-like receptor 4 (TLR4) by lipopolysaccharide, leading to inflammatory cytokines production in the heart. MAC28 is a novel MD2 inhibitor, which had been shown to provide effects against LPS-induced cytokine secretion from macrophages. However, the potential benefits of MAC28 on the LV function and its underlying mechanisms in HFD-induced prediabetic rats are unknown. Purpose: We tested the hypothesis that MAC28 improves LV function in prediabetic rats by reducing cardiac oxidative stress, inflammation, and cardiac mitochondrial dysfunction. Methods: Male Wistar rats were fed either a normal diet (ND, n=8) or HFD (n=24) for 16 weeks. At week 12, HFD-fed rats developed prediabetes and LV dysfunction. At this time, these HFD-fed rats were divided into 3 treatment groups (n=8/group): 1) vehicle (HFDV; 1% Na-carboxymethyl cellulose; p.o.); 2) MAC28 (40 mg/kg; p.o.); 3) metformin (300 mg/kg; p.o.; a positive control), the ND-fed rats received a vehicle (NDV). Rats were received their treatment for 4 weeks. Then, LV function and heart rate variability (HRV) were examined, and the heart was removed to determinecardiac malondialdehyde (MDA), cardiac inflammation (TNF-α) and mitochondrial function. Results: HFD-induced prediabetes, together with depressed HRV and %LV ejection fraction (LVEF) (Fig. 1A). Moreover, cardiac oxidative stress and inflammation overproduction, and cardiac mitochondrial dysfunction was also observed, shown by elevated cardiac MDA, cardiac TNF-α protein levels, and mitochondrial ROS levels, mitochondrial depolarization and swelling (Fig. 1B). Notably, treatment with MAC28 effectively improved HRV and %LVEF and HRV (Fig. 1A), compared to HFDV group. Moreover, MAC28 significantly reduced cardiac MDA levels, cardiac TNF-α protein levels and cardiac mitochondrial dysfunction in HFD-induced prediabetic rats (Fig. 1B). These beneficial effects were also observed in metformin-treated rats (Fig. 1A, B). Conclusion: MAC28 exerts cardioprotection in prediabetic rats by reducing cardiac oxidative stress, inflammation, and mitochondrial dysfunction, leading to restoring LV function. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the Thailand Science Research and Innovation